(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article examines the social foundations of code-switching as a phenomenon emerging in multilingual contexts. The study explores how factors such as age, professional activity, level of education, social identity, digital environment, and cultural influences affect language switching in speech. The findings indicate that code-switching is closely linked to communicative situations and social needs, functioning as a purposeful speech strategy rather than a random occurrence